2005
DOI: 10.1016/j.joca.2005.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes of the low-density lipoprotein receptor-related protein 5 (LRP5) gene: Are they a risk factor in osteoarthritis?

Abstract: A closer investigation of LRP5 and associated Wnt signalling molecules in OA will help determine disease aetiology and the development of novel treatment strategies that specifically target the bone compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 45 publications
3
32
1
1
Order By: Relevance
“…In osteoblasts, LRP5 can transduce canonical signals to promote the renewal of stem cells, the stimulation of pre-osteoblast replication, the induction of osteoblastogenesis, and the inhibition of osteoblast and osteocyte apoptosis by increasing the levels of b-catenin and altering gene expression through the Lef/Tcf transcription factors (Krishnan et al, 2006). The human LRP5 gene is located on chromosome 11q13.4, which consists of 22 introns and 23 exons and spans approximately 160 kb (Smith et al, 2005). Recently, a number of polymorphisms have been described in the LRP5 gene (http://www.ncbi.nlm.nih.gov/SNP).…”
Section: Introductionmentioning
confidence: 99%
“…In osteoblasts, LRP5 can transduce canonical signals to promote the renewal of stem cells, the stimulation of pre-osteoblast replication, the induction of osteoblastogenesis, and the inhibition of osteoblast and osteocyte apoptosis by increasing the levels of b-catenin and altering gene expression through the Lef/Tcf transcription factors (Krishnan et al, 2006). The human LRP5 gene is located on chromosome 11q13.4, which consists of 22 introns and 23 exons and spans approximately 160 kb (Smith et al, 2005). Recently, a number of polymorphisms have been described in the LRP5 gene (http://www.ncbi.nlm.nih.gov/SNP).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been suggested that the Wnt pathway may represent a "bone and joint connection" [7]. On the other hand, an association between certain polymorphisms of Wnt-related genes and the risk of OA has been reported [11][12][13][14][15][16]. Those data prompted us to study the expression of an array of Wnt pathway genes in the bone tissue of patients with osteoporotic fractures and OA and to explore the possible differences in the allelic frequencies of a SNP set capturing the common variations of Wnt receptors and inhibitors in both skeletal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In a large meta-analysis, a weak association in a SNP to hip OA was found (OR = 1.12; p <0.016), but not with other OA sites (Evangelou et al, 2009). Another gene of the Wnt signaling pathway, LRP5, has also been associated with OA (Smith et al, 2005), although the results were unable to be replicated in a large population-based study (Kerkhof et al, 2008).…”
Section: Wnt Signaling Pathwaymentioning
confidence: 96%